Tilt-induced changes in f-wave characteristics during atrial fibrillation: an experimental and computational investigation - Abdollahpur, Mostafa; Celotto, Chiara; Sánchez, Carlos; Plappert, Felix; Östenson, Sten; Platonov, Pyotr G.; Laguna, Pablo; Pueyo, Esther; Sandberg, Frida (Frontiers in Physiology, 2025)
IntroductionThis study explores transient and stationary effects of sympathetic and parasympathetic stimulation on f-wave characteristics in atrial fibrillation (AF) patients undergoing a tilt test. Transient phase is defined as the initial 2-minute interval following each postural change, reflecting immediate autonomic adaptation, whereas steady phase refers to the subsequent interval (from 3 minutes post-change until phase end) representing a stable autonomic state.MethodsOur primary aim is to investigate how the two branches of the autonomic nervous system (ANS) influence the f-wave frequency time series (f(m)). An analysis of f(m) in terms of the mean over time (Ff) and the magnitude of respiration-modulated f(m) variations (ΔFf) is conducted during baseline supine rest (B), head-down tilt (HDT) and head-up tilt (HUT). We analyzed data from a previous study in which 24 patients with persistent AF underwent a tilt test protocol, during which electrocardiograms (ECGs) were recorded. A model-based method was used to extract f(m) series from the ECG. Subsequently, an orthogonal subspace projection method was employed to quantify ΔFf, considering an ECG-derived respiratory signal. Electrophysiological computational simulations were conducted on 2D and 3D human atrial persistent AF models to aid the interpretation of clinical findings. Various levels of cholinergic stimulation by acetylcholine and β-adrenergic stimulation by isoproterenol were tested in the models. The temporal modulation of acetylcholine, representing changes associated with respiration, was cyclically modeled using sinusoidal waveforms.ResultsAnalysis of the clinical data showed a decrease in Ff from B to HDT and an increase from HDT to HUT. During HDT, ΔFf initially increased in the transient phase before decreasing in the steady phase, then rose again during HUT. Analysis of the simulated data showed that increasing the concentration of Isoproterenol and/or acetylcholine resulted in a rise in Ff. Additionally, the magnitude of ΔFf was shown to be associated with the extent of acetylcholine fluctuation.DiscussionThese results suggest that changes in f-wave frequency characteristics during HUT and HDT could be linked to changes in sympathetic activity, with parasympathetic activity possibly modulating the effects of sympathetic activity rather than being an independent driver of fibrillatory rate changes.